2021
DOI: 10.3390/coatings11050577
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Oxidation of Cr-Coated Resistance Upset Welds Made from E110 Alloy

Abstract: The resistance upset welds (RUW) made from E110 alloy without and with Cr coatings were oxidized in air atmosphere at 1100 °C for 2, 10 and 30 min. The cross-section microstructure, elemental composition and hardness were studied before and after oxidation using optical and scanning electron microscopy, and indentations in welding region. The RUW welding does not noticeably change oxidation kinetics of E110 alloy. The most crucial effect has surface non-regularities formed after welding, which prevent uniform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The following parameters of ion source were used: accelerated voltage of 2.5 kV, ion current of 40 mA, and Ar pressure of 0.1 Pa. The procedure of Cr coating deposition was the same as it was in previous studies [26,27]. The obtained Cr coating had a dense and columnar microstructure with a uniform thickness of ~9.8 ± 0.4 µm.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…The following parameters of ion source were used: accelerated voltage of 2.5 kV, ion current of 40 mA, and Ar pressure of 0.1 Pa. The procedure of Cr coating deposition was the same as it was in previous studies [26,27]. The obtained Cr coating had a dense and columnar microstructure with a uniform thickness of ~9.8 ± 0.4 µm.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…The special geometry of the connecting part between the cladding tube and the end plug makes it hard to get a uniform coating on it, making it the weak point of the whole fuel rod in accident conditions. An air oxidation experiment on fully Cr-coated Zr alloy cladding tubes was conducted by Sidelev et al [158] to evaluate the effect of resistance upset welding. Partially oxidation enhancement is found at the weld burr region: the Cr coating at the weld burr region totally disappears, oxygen and nitrogen have diffused into the Zr substrate, forming solutions of α-Zr (O) and α-Zr(N).…”
Section: Local Oxidation Of Welding Zonementioning
confidence: 99%
“…Its detailed description is presented in [24]. Deposition parameters of Cr coating on the LBW E110 alloy samples (Table 1) were selected based on previous results in refs [22,23]. The thickness of the Cr coating was equal to 14.4 µm.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The influence of Cr coating deposition on oxidation behavior (at 1100 • C) of resistance upset (RUW) and laser beam welds (LBW) from Zr alloy was earlier studied in [22,23], which found that the microstructure of welded alloy did not change under Cr coating deposition by magnetron sputtering and high-temperature oxidation of Zr alloy welds can be prevented applying 8 µm-thick Cr coating. However, high-temperature tests had a short duration of the isothermal oxidation stage; it was equal to 2-10 and 2-30 min for LBW and RUW samples, respectively.…”
Section: Introductionmentioning
confidence: 99%